Electronic Literacies in the Workplace - Sullivan, Patricia and Jennie Dautermann (Urbana The National Council of Teachers of English, 1996)
The National Council of Teachers of English. Writing-in-the-work place research has helped us understand professional writing and rhetoric in workplace settings. Inquiries into how people write in particular workplaces have expanded our knowledge of the social facrors in writing and have begun to change the writing instruction of future professionals.
Keywords: Science